USA Cycling (2006)
USA Cycling History The Amateur Bicycle League of America was organized in 1920 and incorporated in New York in 1921. In 1975, the name was changed to the United States Cycling Federation. In 1995, USA Cycling, was incorporated in Colorado, and on July 1, 1995, the two corporations merged, with USA Cycling being the umbrella corporation.